1994
DOI: 10.1007/bf01987633
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of the bicyclic imidazoles on cytokine biosynthesis in human monocytes and endothelial cells

Abstract: Abstract. The effects of bicyclic imidazoles on human monocyte and endothelial cell cytokine production were examined. These compounds constitute the CSAID TM class of anti-inflammatories and are inhibitors of cytokine biosynthesis. The bicyclic imidazoles differ from glucocorticoids and phosphodiesterase inhibitors in their chemical structure as well as pharmacological profile. At optimal concentrations of LPS (50 ng/ml), SK&F 86002, a prototypic compound, inhibited IL-1 and TNF but not g-CSF or IRAP producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Studies of p38 MAPK signaling have been aided by the availability of pyridinyl imidazole compounds that are highly specific inhibitors of p38 MAPK (22). These inhibitors have been shown previously to block production of proinflammatory cytokines in vitro and in vivo (4,12,13,23,24). Young et al (13) reported that pyridinyl imidazole inhibitors reduced endotoxin-induced cytokine production in isolated human PBMC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of p38 MAPK signaling have been aided by the availability of pyridinyl imidazole compounds that are highly specific inhibitors of p38 MAPK (22). These inhibitors have been shown previously to block production of proinflammatory cytokines in vitro and in vivo (4,12,13,23,24). Young et al (13) reported that pyridinyl imidazole inhibitors reduced endotoxin-induced cytokine production in isolated human PBMC.…”
Section: Discussionmentioning
confidence: 99%
“…The pyridinyl imidazoles, typified by SB203580, have proven useful in investigating the role of p38 kinase in regulating transcription, translation, and cytoskeletal elements in response to various stress and cytokine stimuli, as well as its potential role in animal models of inflammatory disease (21)(22)(23)(24)(25)(26). However, there has not been to date a detailed understanding of how SB203580 binds and subsequently inhibits p38 kinase catalytic activity.…”
mentioning
confidence: 99%
“…In IL-1-stimulated U1 cells and human peripheral blood mononuclear cells freshly infected with HIV-1, a specific inhibitor of p38 MAPK suppresses HIV-1 production (38). The pyridinyl imidazole compound SB 203580 specifically binds to and inactivates p38 MAPK (39,40); therefore, U1 cells were preincubated with the p38 MAPK inhibitor (0.00032-5.0 M) for 1 h and then stimulated with IL-18. Cultures were conducted in polypropylene tubes for 24 h. As shown in Fig.…”
Section: Mature But Not Pro-il-18mentioning
confidence: 99%